The emotional intelligence of today’s parents – influences on parenting style and parental competence - Șițoiu, Andreea; Pânișoară, Georgeta (Frontiers in Public Health, 2023)
The emotional intelligence of parents and parental competence become two premises of effective parenting. This study contributes to the understanding of how parents’ emotional intelligence exerts its effect on both their parenting style and parenting competence. The present research also sought to identify the factors that determine the level of parental competence. The research method used is the questionnaire-based survey. The research sample, represented by 610 respondents, was determined by the sampling strategy based on convenience, respectively by the snowball method. The results indicated that the emotional intelligence of parents is associated with an increased level of parental competence (r = 0.24, p < 0.001), and 15% of the variability of parental competence is determined by the level of parental emotional intelligence (R = 0.38, p < 0.00, R2 = 0.15). It was demonstrated that 6% of the variability of parental competence is determined by the level of parents’ self-esteem (R = 0.24, p < 0.001, R2 = 0.06). The emotional intelligence and self-esteem of the parents contribute to the development of a high level of parental competence, while the level of education of the respondents according to this research partially influences the development of parental competence. Despite the fact that a high educational level of parents is assumed to give them access to quality information, the Barnum effect is experienced regardless of educational level. According to the field of parenting, the Barnum effect refers to consulting non-scientifically validated sources and trusting information that responds to parents’ wishes, but not to children’s educational needs.These results highlight the role of parents’ emotional intelligence on the growth and education of children, but also the usefulness of training programs in the field of parenting with the aim of training parents in the necessary skills for effective parenting.